REVISÃO DA FISIOTERAPIA NA MIASTENIA GRAVE (Movimenta (ISSN 1984-4298), 2018)
This paper presents a brief review of the Physical Therapy work in Myasthenia Gravis, a progressive muscular weakness disease. Seventeen papers were investigated from the national and international literature. Three of these articles showed that the Physical Therapy, both the motor and the respiratory, was an important tool for improving life’s quality, by motor system improvement, fatigue and respiratory injuries reduction, according to the 10-point fatigue scale, the manual muscle strength tests, the lung injury score and other respiratory variables. However, the lack of scientific evidences of the Physical Therapy’s benefits confirms the needing for further researches, especially about the Physical Therapy’s action after or before the hospital interned period in order to diminish the effects of the disease’s progression.